Scaffolding individuality: coordination, cooperation, collaboration and community. (13th March 2023) - Griesemer, James; Shavit, Ayelet
Abstract : Processes of evolutionary transition (ET), becoming part of a new reproducing collective while losing the capacity of independent reproduction, seem difficult to track without circularity, since their features—units of selection, individuality, inheritance at multiple levels (MLS1, MLS2)—are products of one process. We describe ET in a non-circular way, noting kinds of interactions among community members necessary for such major transitions that are not instances of those same interactions within community members. Reproducing 'systems' tend to hybridize with environmental components, employing eco–devo scaffolding interactions forming communities. Communities are developmentally scaffolded systems of diverse members engaged in heterogeneous interactions. They may become individuals in their own right with the potential to evolve an inheritance system at the emergent community level. We argue for the explanatory benefits of treating 'individuality' as a special case of 'collectivity'. We characterize an idealized sequence of collective processes—coordination, cooperation and collaboration (3Cs)—which scaffolds transitions to new forms of collective individuality: communities. Hominid evolution and learning draw attention to developmental interactions driving both dimensions of ET: new 'levels of individuality' and inherited 'information systems'. Here, we outline a theoretical perspective that we suggest applies across a wide range of cases and scenarios. This article is part of the theme issue 'Human socio-cultural evolution in light of evolutionary transitions'.